2022
DOI: 10.2478/rtuect-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Assessments under the United Nations Sustainable Development Goals: A Bibliometric Analysis

Abstract: The United Nations announced its 2030 Agenda for Sustainable Development worldwide in 2015. Comprehensive assessments of member states’ performance towards achieving the related UN Sustainable Development Goals (SDGs) have since become a major challenge for national and subnational governments. This article presents a bibliometric analysis on the assessment of SDGs, at both the general and specific levels, based on 418 publications obtained from Scopus. The general level of analysis includes the number, types,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…These results show progress and a trend in SDGs studies, pointing to a growth in environmental research. Similar findings have been reported in previous studies by Sweileh ( 2020 ), Londono-Pineda and Cano ( 2022 ), and Yamaguchi et al ( 2023 ). However, Yamaguchi et al ( 2023 ) focused on the most cited articles, and Sweileh ( 2020 ) only analyzed articles with the phrase “sustainable development goal”, while this study has a broader scope.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results show progress and a trend in SDGs studies, pointing to a growth in environmental research. Similar findings have been reported in previous studies by Sweileh ( 2020 ), Londono-Pineda and Cano ( 2022 ), and Yamaguchi et al ( 2023 ). However, Yamaguchi et al ( 2023 ) focused on the most cited articles, and Sweileh ( 2020 ) only analyzed articles with the phrase “sustainable development goal”, while this study has a broader scope.…”
Section: Discussionsupporting
confidence: 92%
“…However, Yamaguchi et al ( 2023 ) focused on the most cited articles, and Sweileh ( 2020 ) only analyzed articles with the phrase “sustainable development goal”, while this study has a broader scope. In addition, Londono-Pineda and Cano ( 2022 ) analyzed the main methodologies used for evaluating SDGs through bibliometric analysis. Scopus and Web of Science were identified by El Mohadab et al ( 2020 ) as the primary databases for bibliometric analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formal and informal institutions are essential to implement a model favoring For some authors, sustainable development and sustainability concepts can be treated as similar (Holden et al 2018). However, sustainable development implies development as a priority, and it represents one of the alternative theories of development, while the concept of sustainability considers the environment as a priority (Cano and Londoño-Pineda 2020;Londoño-Pineda and Cano 2022). Based on this rationale, this study follows Shaker's conceptualization (Shaker 2015), which suggests that sustainability is the goal and sustainable development is the process to reach it.…”
Section: Concepts and Capitals Involved In Rural Entrepreneurship And...mentioning
confidence: 99%
“…Previous bibliometric studies have reported that research related to the SDGs is focused mainly on health (SDG 3), climate change (SDG 13), food (SDG 2), energy (SDG7), and sanitation (SDG 6) (Meschede 2020;Belmonte-Ureña et al 2021;Yeh et al 2022;Londoño-Pineda and Cano 2022;Sianes et al 2022). Controversially, the present research found that academic research on SDGs 8, 9, 11, which was considered poorly researched and lacking in consolidated literature (Pizzi et al 2020), obtained greater evidence, despite the number of occurrences and citations that can lead to an erroneous conclusion.…”
Section: Introductionmentioning
confidence: 99%